Implementation of Discovery Learning Models to Improve Student Learning Outcomes on Additive Materials and Addicitive Substances Topic in 8th Grade As Shiddiqiyah Junior High School - Dewi Apriana; Sri Wardhani; Haryadi Haryadi (BIODIK, 2019)
This study is a type of Classroom Action Research (CAR) which aimed to improve students' attitudes, skills and knowledge on additives and addictive substances using Discovery learning model. This study was conducted in 2 cycles, each cycle consists of 4 stages: planning, action, observation and reflection. The subjects of this study were eighth grade students of As Shiddiqiyah Junior High School in the first semester with a total of 30 students. Data analysis was carried out with quantitative descriptive techniques. Based on the results of the study, it was found that the attitude of students in the learning process had increased, it was known from the results of the average classroom observations in the first cycle was 68.15 which had an increase in the second cycle to 81.14. The skills of students in the first cycle obtained an average yield of 71.36 which increased in cycle II to 84.11. The results of the written test in the first cycle of students' cycles were 59.61 in the second cycle to 81.07. The percentage value in the cycle is 31%, and increases in cycle II by 82%. Based on this study, classical achievement had exceeded 75%, it can be concluded that there is an increase in learning outcomes from the attitudes, skills and knowledge of students in additives and addictive substances in 8th grade As Shiddiqiyah Junior High School. Keywords: Discovery Learning, Attitudes, Skills, Knowledge, Additives and Addictive Substances Abstrak. Tujuan untuk meningkatkan sikap, keterampilan dan pengetahuan siswa pada materi zat aditif dengan menggunakan model pembelajaran Discovery Learning. Metode penelitian menggunakan penelitian tindakan kelas (PTK) yang dilaksanakan dalam 2 siklus, tiap siklusnya terdiri dari 4 tahap yaitu perencanaan, pelaksanaan tindakan, observasi dan refleksi. Subyek dari penelitian ini adalah siswa kelas VIII SMP As Shiddiqiyah semester I Tahun pelajaran 2018/2019 dengan jumlah siswa sebanyak 30 orang. Analisis data dilakukan dengan teknik deskriptif kuantitatif. Berdasarkan hasil penelitian diperoleh ranah sikap siswa pada proses belajar mengalami peningkatan, diketahui dari hasil observasi rata-rata kelas pada siklus I adalah sebesar 68,15 mengalami peningkatan di siklus II menjadi 81,14. Keterampilan siswa pada siklus I memperoleh hasil rata-rata sebesar 71,36 mengalami peningkatan disiklus II menjadi 84,11. Hasil tes tertulis siswa disiklus I nilai rata-rata yang diperoleh adalah 59,61 di siklus II menjadi 81,07. Nilai persentase di siklus sebesar 31% , dan meningkat di siklus II sebesar 82%. Berdasarkan penelitian ini pencapaian klasikal telah melampaui 75% , dapat disimpulkan bahwa ada peningkatan hasil belajar dari sikap, keterampilan dan pengetahuan siswa pada materi zat aditif dan zat adiktif dikelas VIII SMP As Shiddiqiyah dalam kategori baik sekali. Kata Kunci: Discovery Learning, Sikap, Keterampilan, Pengetahuan, Zat Aditif dan Zat Adiktif.